Lanthanide‐doped rare earth nanoparticles for near‐infrared‐II imaging and cancer therapy - Zhao, Hongxia; Xiao, He; Liu, Ying; Ju, Huangxian (BMEmat (Print), 2023)
The optical nanoprobes with emissions in the second near‐infrared window (NIR‐II, 1000–1700 nm) show low tissue autofluorescence and photon scattering; therefore, they provide high spatial resolution and acceptable tissue penetration depth. These advantages make them appropriate for in vivo applications, including bioimaging, NIR‐II triggered disease therapy, and even on‐site efficacy monitoring. Among the various developed NIR‐II fluorescence probes, lanthanide‐doped nanoparticles (LDNPs) exhibit high photo stability and narrow emission bandwidths with long photoluminescence lifetimes and low cytotoxicity; therefore, they have been widely studied in the biomedical field. This review summarizes the typical compositions and optical properties of recently developed NIR‐II emitting LDNPs. Their applications in in vivo NIR‐II bioimaging and cancer therapy are reviewed. The perspectives and challenges of NIR‐II LDNPs are also discussed. Lanthanide‐doped nanoparticles (LDNPs) offer various emissions in the NIR‐II region by co‐doping different rare earth metal ions. This review summarizes different sensitizer ions for LDNPs with NIR‐II emissions, and their applications in “always on” in vivo imaging, activatable in vivo imaging, and NIR‐II imaging‐guided therapy. NIR‐II imaging guided theranostics provides controllable responsiveness, high resolution, improved penetration depth and low background interference.